Tactile Sensors Based on Conductive Polymers - Macicior, Haritz; Sikora, Tomasz; Ochoteco, Estíbalitz; Castellanos-Ramos, Julián; Navas-González, Rafael Jesús; Vidal-Verdú, Fernando (Springer Berlin / Heidelberg, 2010)
This paper presents results from a selection of tactile sensors that have been designed and fabricated. These sensors are based on a common approach that consists in placing a sheet of piezoresistive material on the top of a set of electrodes. We use a thin film of conductive polymer as the piezoresistive mate¬rial. Specifically, a conductive water-based ink of this polymer is deposited by spin coating on a flexible plastic sheet, giving it a smooth, homogeneous and conducting thin film. The main interest in this procedure is that it is cheap and it allows the fabrication of flexible and low cost tactile sensors. In this work we present results from sensors made using two technologies. Firstly, we have used a flexible Printed Circuit Board (PCB) technology to fabricate the set of electrodes and addressing tracks. The result is a simple, flexible tactile sensor. In addition to these sensors on PCB, we have proposed, designed and fabricated sensors with screen printing technology. In this case, the set of electrodes and addressing tracks are made by printing an ink based on silver nanoparticles. The intense characterization provides us insights into the design of these tactile sensors.
Keywords: Transductores de presión; Tactile sensors based on conductive polymers; Sensors fabricated with printed circuit board technology; Sensors fabricated with screen-printing technology